2022
DOI: 10.3390/molecules27217600
|View full text |Cite
|
Sign up to set email alerts
|

Application of Density Measurements for Discrimination and Evaluation of Chemical Composition of Different Types of Mechanically Separated Meat (MSM)

Abstract: At present, the problem of identifying and controlling different types of Mechanically Separated Meat (MSM) is a very important practical issue in the meat industry. To address this challenge, the authors propose a new, analytical method for the discrimination and characterization of MSM that uses density measurements. The method proposed by the authors, in contrast to the analytical methods existing so far, is rapid, non-destructive, relatively simple and can be computerized. The density measurements of meat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, MSM is not equivalent to manually boned meat. A study evaluating the chemical composition of MSM through density measurements, found that manually boned meat, in relation to all types of MSM, is characterized by higher density, higher protein content and lower sodium, calcium and fat content 2 . Therefore, replacing manually boned meat with MSM cannot be justified as an improvement in nutritional composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, MSM is not equivalent to manually boned meat. A study evaluating the chemical composition of MSM through density measurements, found that manually boned meat, in relation to all types of MSM, is characterized by higher density, higher protein content and lower sodium, calcium and fat content 2 . Therefore, replacing manually boned meat with MSM cannot be justified as an improvement in nutritional composition.…”
Section: Discussionmentioning
confidence: 99%
“…MSM is used as an ingredient in a variety of meat products and may have a significant impact on their quality, as well as on consumer satisfaction and safety 1 . Due to its low cost, MSM is widely used in the food industry 2 and is commonly used in meat processing around the world, mainly in cooked or roasted meat products, canned meat, homogenized sausages, frankfurters, bologna, nuggets, patties and many other ready-to-eat ultra-processed food products 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Bone fragments in meat can also be detected by X-ray microtomography [ 7 , 10 ] and ESR spectroscopy [ 8 ]. The type of MSM can be identified by measuring the density and velocity of ultrasound waves [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%